Why You Can't Find That Nice Bottle of South African Wine. (November 2019) - Finlay, William; Pandian, Kavi
South African wine producers are more successful in the American market when they partner with importers that know little about their wines. Ignorance is better than expertise, and leads to a handful of wineries being very successful in the market, while most barely make a splash.